2014
DOI: 10.5120/16556-1441
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Quality Healthcare Services using Clinical Pathways

Abstract: The aim of this paper is to investigate clinical pathways as a tool to improve the healthcare quality, is a need for a method to improve patient safety, healthcare quality, and efficiency of medical activities, in healthcare there is a change in the method of looking to the services, the services in healthcare shifting from structure to process to outcomes. Result from investigating literature review reveal characteristics of clinical pathways and the method of presentation will improve healthcare quality. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…CP specifies what must be done in certain clinical conditions and provides a treatment plan with service standards considered in accordance with evidence-based medicine (EBM) [14]. According to Mater, the first thing that needs to be done is to improve the quality of medical staff with knowledge related to CP before carrying out a good clinical pathway implementation [15]. So, it can be concluded that the content still needs to be improved, especially by determining the allocation of resources to train staff in the use of the CP form.Based on the ICPAT assessment, in dimension 5, the percentage of content is 25% and quality is 69%.…”
Section: Discussionmentioning
confidence: 99%
“…CP specifies what must be done in certain clinical conditions and provides a treatment plan with service standards considered in accordance with evidence-based medicine (EBM) [14]. According to Mater, the first thing that needs to be done is to improve the quality of medical staff with knowledge related to CP before carrying out a good clinical pathway implementation [15]. So, it can be concluded that the content still needs to be improved, especially by determining the allocation of resources to train staff in the use of the CP form.Based on the ICPAT assessment, in dimension 5, the percentage of content is 25% and quality is 69%.…”
Section: Discussionmentioning
confidence: 99%
“…The method of presenting CPs must therefore be adapted to the needs and knowledge of very diverse recipients (patients, doctors, medical personnel) and also, as the research conducted by the authors has shown, to the context of its use (Szela ˛gowski and Berniak-Wo zny, 2019). Therefore, when modeling a CP, its legibility and standardization are extremely important, as is the ability to adjust the method and scope of the presented information to the context of its use (Mater and Ibrahim, 2014). The method of modeling CPs must take into account their unstructured and knowledge-intensive nature (Berniak-Wo zny and Szela ˛gowski, 2022; Andellini et al, 2017;Kirchmer et al, 2013;Mans et al, 2008).…”
Section: Proposal Of Bpmn Extensionmentioning
confidence: 99%
“…In the first dimension, it can be seen that although the informants have understood the identification of clinical pathways, they are not necessarily in line with the quality produced. Improvements can be made through the provision of periodic training to improve the process and quality of patient documentation outcomes (Mater and Ibrahim, 2014). A study in Nigeria reported that the blended learning approach was quite effective in increasing the knowledge and competence of each healthcare professional on clinical pathways (Eguzo et al, 2021).…”
Section: Content and Quality Evaluationmentioning
confidence: 99%